Exopolysaccharides from Klebsiella oxytoca: anti-inflammatory activity - Thays Avelino Bannwart; Ciomar Aparecida Bersani-Amado; Franciele Queiroz Ames; Vera Lúcia Dias Siqueira; Arildo José Braz de Oliveira; Regina Aparecida Correia Gonçalves (Universidade de São Paulo, 2022)
Abstract Exopolysaccharides (EPS) produced by Klebsiella oxytoca are of environmental, pharmaceutical, and medicinal interest. However, studies about the anti-inflammatory activity of EPS produced by this microorganism still remain limited. The aim of this study was to produce, characterize, and evaluate the anti-inflammatory activity of EPS from K. oxytoca in a pleurisy model. Colorimetric analysis revealed that precipitated crude exopolysaccharides (KEPSC) and deproteinated exopolysaccharides (KEPS) present high levels of total carbohydrates (65.57% and 62.82%, respectively). Analyses of uronic acid (7.90% in KEPSC and 6.21% in KEPS) and pyruvic acid (3.01% in KEPSC and 1.68% in KEPS) confirm that the EPS are acidic. Gas chromatography-mass spectrometry analyses demonstrated that the EPS consisted of rhamnose (29.83%), glucose (11.21%), galactose (52.45%), and mannose (6.50%). The treatment of an experimental pleurisy model in rats through subcutaneous administration of 50, 100, 200, and 400 mg/kg of KEPS decreased both the volume of inflammatory exudate and the number of leukocytes recruited to the pleural cavity. The present data showed that EPS production by K. oxytoca using the method described is easy to perform and results in a good yield. In addition, we show that KEPS exhibit anti-inflammatory activity when administered subcutaneously in rats.